2013
DOI: 10.1097/pgp.0b013e31825d8064
|View full text |Cite
|
Sign up to set email alerts
|

Cellular FLICE-like Inhibitory Protein Long Form (c-FLIPL) Overexpression is Related to Cervical Cancer Progression

Abstract: Cervical cancer is a leading cause of cancer deaths in women worldwide and infection by high-risk human papillomavirus types is a precursor event. The cellular FLICE-like inhibitory protein (c-FLIP) has been found to be overexpressed in several types of cancers and could be associated with cervical cancer progression because of its ability to inhibit the apoptotic process. To detect c-FLIP expression in cervical cancer, an immunohistochemical staining was performed, using tissue microarrays, on a series of 536… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In one study of 462 colorectal cancer patients, FLIP(L) was identified as an independent marker of poor prognosis, whereas FLIP(S) (and TRAIL receptor) expression did not show a significant correlation with prognosis [121]. In a study of 536 cervical carcinoma samples, FLIP(L) expression increased in line with the grade of the carcinoma, although no significant relationship between FLIP and patient survival could be established [133]. In addition, in a study by our group, FLIP(L) mRNA was shown to significantly correlate with poorer overall survival of a cohort of AML patients [130].…”
Section: Flip Expression and Drug Resistance In Cancermentioning
confidence: 99%
“…In one study of 462 colorectal cancer patients, FLIP(L) was identified as an independent marker of poor prognosis, whereas FLIP(S) (and TRAIL receptor) expression did not show a significant correlation with prognosis [121]. In a study of 536 cervical carcinoma samples, FLIP(L) expression increased in line with the grade of the carcinoma, although no significant relationship between FLIP and patient survival could be established [133]. In addition, in a study by our group, FLIP(L) mRNA was shown to significantly correlate with poorer overall survival of a cohort of AML patients [130].…”
Section: Flip Expression and Drug Resistance In Cancermentioning
confidence: 99%
“…c-FLIP variants are also expressed in pancreatic intraepithelial neoplasms as well as pancreatic ductal adenocarcinomas, while c-FLIP was not detected in normal pancreatic ducts [77]. While the epithelium of the normal cervix and low-grade squamous intraepithelial lesions were mainly negative for c-FLIP, high-grade intraepithelial lesions as well as cancer samples showed increased c-FLIP expression [78]. This finding suggests that c-FLIP expression may serve as a potential cervical cancer progression marker.…”
Section: Upregulation Of C-flip In Human Cancersmentioning
confidence: 99%
“…Alternatively increased expression of the anti-apoptotic protein c-FLIP can function upstream of caspase-8 to decrease apoptosis signaling [73]. Interestingly c-FLIP shows variable expression depending on tumor type and may represent a key mechanism of TRAIL-specific tumor escape [74,75,76]. Alternative mechanisms for resistance to TRAIL-mediated apoptosis includes the overexpression of the anti-apoptotic proteins Bcl-2 and Bcl-XL, both of which function to prevent mitochondrial release of cytochrome C and activation of the intrinsic apoptosis pathway [77,78].…”
Section: Modulation Of Tumor Necrosis Factor (Tnf)-related Apoptosmentioning
confidence: 99%